Sesamol Inhibits Aβ1-42-Induced Ferroptosis by Regulating the SLC7A11/GPX4/ACSL4 Axis in PC12 Cells - ZHAO Peijun, WANG Tianlin, XIE Shanshan, SONG Lianjun, HUANG Xianqing, LI Tiange (Shipin Kexue)
The purpose of this study was to investigate the effect and mechanism of sesamol (SE) on amyloid-β (Aβ) induced ferroptosis in pheochromocytoma (PC12) cells. A PC12 cell of ferroptosis induced by erastin, RSL-3 or Aβ1-42 was established and evaluated by the CCK-8 method, and the effective protective dose of SE was determined. The inhibitory effect of SE on lipid peroxidation was detected by flow cytometry and enzyme linked immunosorbent assay. The protective effect of SE on mitochondria was observed by fluorescence microscopy and transmission electron microscopy. The effect of SE on the mRNA and protein expression of transferrin receptor protein 1 (TFR1), divalent metal-ion transporter 1 (DMT1), ferroportin (FPN), glutathione peroxidase 4 (GPX4), solute carrier family 7 member 11 (SLC7A11) and acyl-CoA synthetase long-chain family member 4 (ACSL4) was detected by real-time quantitative polymerase chain reaction and Western blot. The results showed that SE significantly inhibited ferroptosis in a dose-dependent manner, and significantly reversed the increase in malondialdehyde levels, the decrease in glutathione content, and the increase in lipid peroxides induced by Aβ1-42. Meanwhile, SE inhibited the loss of mitochondrial membrane potential and protected mitochondrial morphology. It also down-regulated the mRNA and protein expression of TFR1, DMT1, and ACSL4, but up-regulated those of FPN, SLC7A11 and GPX4. In conclusion, sesamol inhibits Aβ1-42-induced ferroptosis by maintaining iron homeostasis and suppressing lipid peroxidation.